2018
DOI: 10.5430/jha.v7n6p16
|View full text |Cite
|
Sign up to set email alerts
|

Successful hospital readmission reduction initiatives: Top five strategies to consider implementing today

Abstract: Only one quarter of U.S. hospitals demonstrated low enough levels of 30 day readmission rates to avoid penalties imposed by the Hospital Readmissions Reduction Program (HRRP) in 2016. Previous work describes interventions for reducing hospital readmission rates; however, without a comprehensive analysis of these interventions, healthcare leaders cannot prioritize strategies for implementation within their healthcare environment. This comparative study identifies the most effective interventions to reduce unpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…The detailed information for the studies finding beneficial outcomes in readmission reductions are listed in Table 3. Kash et al [44] Overall, there were significantly reduced admission and readmission rates for patients with the pure CHF diagnosis; 30-day and 90-day readmission rates declined 75% (p = .02) and 74% (p = .004), respectively. Reductions were also seen in total hospital days and emergency room utilization.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The detailed information for the studies finding beneficial outcomes in readmission reductions are listed in Table 3. Kash et al [44] Overall, there were significantly reduced admission and readmission rates for patients with the pure CHF diagnosis; 30-day and 90-day readmission rates declined 75% (p = .02) and 74% (p = .004), respectively. Reductions were also seen in total hospital days and emergency room utilization.…”
Section: Resultsmentioning
confidence: 93%
“…A list and description of the interventions aimed toward reducing short-term hospital readmissions can be found in Kash et al's study. [43,44] A breakdown of the number of studies examining various strategies and the number finding beneficial, null, or mixed effects can be found in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, previous evidence showed that pre-discharge patient/family education is a successful intervention to reduce preventable readmission [42,43]. Therefore, it would be important for hospital leaders or health care workers in children's hospitals to consider emphasizing the contents related to ambient air pollution when delivering education to the children with asthma and their family before discharge as one of the readmission reduction initiatives.…”
Section: Health Policy and Practice Implicationsmentioning
confidence: 99%
“…Therefore, collaboration between clinical and community partners (e.g. PCPs, nonprofit organizations, and educators) for transitional care and followup would contribute to reducing repeated hospital admissions since appropriate care for asthma management in the community, such as asthma education, can prevent repeated hospitalizations (49)(50)(51).…”
Section: Implications For Healthcare Systemmentioning
confidence: 99%